THEMATIC PROGRRESSION PATTERNS IN RADAR MADURA ARTICLE - Athena, Tera; Kiptiyah, Mariyatul (Jurnal Sastra Aksara, 2019)
The skill to arrange sentences in language is very much determined by how the speaker or writer uses the language grammatically correctly, that is, prioritizing coherence and coherence. In this ability, the writer or speaker must be able to develop sentence 1 to the next sentence by putting forward a continuous flow and can understand the message of what was written. In Discourse Analysis there is the term Theme which is something that is discussed, the point of departure for clauses as messages and Rheme is part of clauses and other grammatical structures. In a text or paragraph the development of the first sentence occurs to the next sentence with a different arrangement of themes and rhemes but still prioritizes coherence and coherence. This development process is called the Thematic Progression Pattern. The researcher analyzes the forms of the Thematic Progression Pattern in two articles in the Madura Radar print media and describes how they are analyzed. From the results of the analysis, it can be seen that the authors of the two articles use themes and interpersonal themes to develop sentences into paragraphs. In the development of sentence 1 into new sentences that coherently form a split theme on the theme progression.